Enhancing neurorehabilitation by targeting beneficial plasticity - Wolpaw, Jonathan R.; Thompson, Aiko K. (Frontiers in Rehabilitation Sciences, 2023)
Neurorehabilitation is now one of the most exciting areas in neuroscience. Recognition that the central nervous system (CNS) remains plastic through life, new understanding of skilled behaviors (skills), and novel methods for engaging and guiding beneficial plasticity combine to provide unprecedented opportunities for restoring skills impaired by CNS injury or disease. The substrate of a skill is a distributed network of neurons and synapses that changes continually through life to ensure that skill performance remains satisfactory as new skills are acquired and as growth, aging, and other life events occur. This substrate can extend from cortex to spinal cord. It has recently been given the name “heksor.” In this new context, the primary goal of rehabilitation is to enable damaged heksors to repair themselves so that their skills are once again performed well. Skill-specific practice, the mainstay of standard therapy, often fails to optimally engage the many sites and kinds of plasticity available in the damaged CNS. New noninvasive technology-based interventions can target beneficial plasticity to critical sites in damaged heksors; these interventions may thereby enable much wider beneficial plasticity that enhances skill recovery. Targeted-plasticity interventions include operant conditioning of a spinal reflex or corticospinal motor evoked potential (MEP), paired-pulse facilitation of corticospinal connections, and brain-computer interface (BCI)-based training of electroencephalographic (EEG) sensorimotor rhythms. Initial clinical studies in people with spinal cord injury, stroke, or multiple sclerosis show that these targeted-plasticity interventions can enhance skill recovery beyond that achieved by skill-specific practice alone. After the intervention ends, the benefits persist.